Driving from the backseat: an exploratory study of the dearth of Malaysian women in political decision making process - Imam-Tamim, Muhammad Kamaldeen; Mohd Zin, Najibah; Ibrahim, Norliah; Che Soh @ Yusoff, Roslina (Asian & African Research Centre, 2015)
The place of women in decision making at various strata of living has been a front burner issue in the current milieu. Population of women in Malaysia is almost as equal the population of men. The Malaysian women have been found to excel in academic and even professional labour market than the men. Thus, they are naturally imbued with the skills and intellectual capabilities to contribute to the Malaysian national development. Notwithstanding the perceived superiority in the intellectual capability of the Malaysian women, the number of women allowed to participate in nation building in the country is abysmally low. Researches have shown that the women have been facing challenges in assuming political positions where they can adequately and practically contribute to national development. The paper involves an exploratory legal research. Therefore, employing an analysis of both primary and secondary documentary data, the paper investigates the factors that contribute to the inhibition of Malaysian women in this regard despite their landmark educational and professional progression and achievement. The paper argues that Malaysia will profit in its national development and nation building programmes if more women are allowed to participate in national governance. There is therefore the need to introduce fresh approaches and perspectives to the current efforts by the Malaysian government to ensure that it keeps up with its commitment towards the millennium development goals.